The Impact of Accumulated Mutations in SARS-CoV-2 Variants on the qPCR Detection Efficiency - Cao, Liu; Xu, Tiefeng; Liu, Xue; Ji, Yanxi; Huang, Siyao; Peng, Hong; Li, Chunmei; Guo, Deyin (Frontiers in Cellular and Infection Microbiology, 2022)
SARS-CoV-2 is evolving with mutations throughout the genome all the time and a number of major variants emerged, including several variants of concern (VOC), such as Delta and Omicron variants. In this study, we demonstrated that mutations in the regions corresponding to the sequences of the probes and 3’-end of primers have a significant impact on qPCR detection efficiency. We also found that the G28916T mutation of the N gene accounts for 78.78% sequenced genomes of Delta variant. It was found that detection sensitivity of G28916T mutant was 2.35 and 1.74 times less than that of the wt sequence and detection limit was reduced from 1 copy/μl to 10 copies/μl for the commercially available CP3 and CP4 primer/probe sets. These results indicate that the detection probes and primers should be optimized to keep maximal detection efficiency in response to the emergence of new variants.